2005
DOI: 10.1016/s0002-9440(10)62949-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Metallothionein Synthesis in Streptozotocin-Induced Diabetic Mice, and Its Protection against Diabetes-Induced Cardiac Injury

Abstract: Oxidative stress is involved in the pathogenesis of diabetes and its cardiovascular complications. Metallothionein (MT), a stress-response protein, is significantly increased in the liver and kidney of diabetic animals. We examined whether diabetes also induces cardiac MT synthesis through oxidative damage and whether MT overexpression protects the heart from injury. Diabetes was induced in mice by single injection of streptozotocin (STZ), and cardiac MT mRNA and protein levels were measured 2 weeks and 2 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 53 publications
11
62
0
Order By: Relevance
“…Using mZDF rats, angiotensinogen was recently shown to be induced in mesangial cells via ROS/ ERK/JNK pathways (Ohashi et al 2010), and similar mechanisms might be operating in the liver. MT1 is a potent cellular antioxidant that plays important roles in essential trace element homeostasis, metal detoxification and in the protection against various injuries resulting from ROS (Chiaverini & De Ley 2010), including the development of diabetes and its complications (Ohly et al 2000, Cai 2004, Song et al 2005, Ayaz et al 2006, Tang et al 2010. It has also been shown that levels of MT1 are increased in the livers of diabetic rats (Cai et al 2002), which is in agreement with the results obtained in this study.…”
Section: Resultssupporting
confidence: 91%
“…Using mZDF rats, angiotensinogen was recently shown to be induced in mesangial cells via ROS/ ERK/JNK pathways (Ohashi et al 2010), and similar mechanisms might be operating in the liver. MT1 is a potent cellular antioxidant that plays important roles in essential trace element homeostasis, metal detoxification and in the protection against various injuries resulting from ROS (Chiaverini & De Ley 2010), including the development of diabetes and its complications (Ohly et al 2000, Cai 2004, Song et al 2005, Ayaz et al 2006, Tang et al 2010. It has also been shown that levels of MT1 are increased in the livers of diabetic rats (Cai et al 2002), which is in agreement with the results obtained in this study.…”
Section: Resultssupporting
confidence: 91%
“…STZ-treated mice with whole blood glucose equal to and higher than 250 mg/dl were considered as diabetic. Mice serving as vehicle controls were given the same volume of sodium citrate [13]. Experimental measurements were performed in the control and diabetic mice 2 weeks after STZ treatment.…”
Section: Animalsmentioning
confidence: 99%
“…We have shown that over-expression of metallothionein (MT) by zinc or through transgenics prevents diabetic cardiomyopathy [12][13][14]. MT is a small protein rich in cysteine content primarily for essential metal homeostasis and heavy metal detoxification.…”
Section: Introductionmentioning
confidence: 99%
“…Heart tissue sections at 4 μm were used to perform immunohistochemical staining for CTGF based on our previous method (Zhou et al, 2004;Song et al, 2005) with the following specific antibody: goat anti-rat CTGF antibodies (Santa Cruz Biotechnology, Santa Cruz CA). Color was developed by incubating with diaminobenzidine and counterstaining with hematoxylin.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…Controls were obtained by replacing the primary antibody with PBS. Semi-quantitative analysis of the percentage of positive staining area was evaluated by computer imaging analysis system (Image Proplus), as described previously (Zhou et al, 2004;Song et al, 2005).…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%